Africa's challenge to international relations theory - edited by Kevin C. Dunn (Houndmills Palgrave, 2013)
Africa has been noticeably absent in international relations theory. This new collection of essays by contemporary Africanists convincingly demonstrates the importance of the continent to every theoretical approach in international relations. This collection breaks new ground in how we think about both international relations and Africa, re-examining such foundational concepts as sovereignty, the state, and power; critically investigating the salience of realism, neo-liberalism, liberalism in Africa, and providing new thinking about regionalism, security and identity.
Includes bibliographical references (pages 220-238) and index.
Keywords: International relations--Philosophy.